The Impact of Factors Affecting Internal Marketing on the Quality of Health Services Provided By Public Hospitals in Amman: An Applied Study - Alomari, Mazen; Falah Al-Zoubi; Fakhrieh Majed Darabseh, Ali (British Journal of Marketing Studies, 2018)
The present study aims to identify the impact of factors affecting internal marketing on the quality of health services provided by the public hospitals in Amman. The problem of the study represents by the low level of health services provided by public hospitals in Amman compared with the health services provided by private hospitals. The population of the study includes all public hospitals in Amman (6 hospitals). The sample of the study was (360) people who were working in these hospitals. The study tool was a questionnaire. The study carried out several conclusions and recommendations including: There is a low level of internal interaction and teamwork among workers in the hospitals as the arithmetic mean of opinions and trends of the study sample was (2.23) on the five-point Likert Scale. There is a low level of participation in decision making for workers in the hospitals as the arithmetic mean of opinions and trends of the sample was (2.90) on the same scale, There is a need to design and find job descriptions for all employees in different disciplines in a manner that allows them to be filled with the right individuals and a need for clarity of the role required from each individual. Planning, implementation and evaluation of training programs on a continuous basis aim at developing employees’ technical and behavioural skills in public hospitals that increasing the level of reliability and responsiveness to them as well as planning and implementation of the satisfaction of workers, both material and moral, for employees who achieve outstanding performance in providing health services in a suitable manner for patients. There is a need for a two-way communication between employees and hospital management, which allows finding quick solutions for work problems and reflects suggestions of employees.